“I’M GOING THROUGH CHANGES”: YOUNG ADULTS’ PATHS TO BELONGING FOLLOWING RESIDENTIAL RELOCATION - Argenio, John P., author; Pennington, Natalie, advisor; Knobloch, Katherine, committee member; O’Callaghan, Erin, committee member (Colorado State University. Libraries, 2026)
Much research has been completed assessing the way individuals manage their need to belong, and what it means to belong. This study adds to that literature by focusing on young adults and their paths to belonging following voluntary residential relocation. The goals of this project were as follows: understand how individuals managed old and new relationships, and how individuals experienced community, combining to represent how young adults experienced belonging in its totality. Using qualitative research methods, 15 in-depth interviews were conducted. Through thematic analysis of 317 pages of transcripts, the interviews revealed a complicated journey towards belonging. Participants first described their complex use of social resources—time and energy—as they managed their changing old and new relationships in their desire for social connection and thus belonging. Furthermore, participants recounted their complicated relationships with social groups and place, as they sought a sense of community. In total, the findings revealed the intertwined roles both people and place play in a young adult’s path to belonging after they relocate. At heart, this exploratory study emphasizes the individualized choices and experiences young adults go through as they move, highlighting the role belongingness plays during a volatile period of their lives.
Keywords: Communication; Residential Relocation; Young Adult; Community; Belonging; Social Ties